UTILIZATION OF VILLAGE FUNDS IN COMMUNITY EMPOWERMENT IN BATU PUTE VILLAGE, SOPPENG RIAJA DISTRICT, BARRU REGENCY. - Asriani; Aidah, Hj.; Jumria; Adrianto (P3M Stia Al Gazali Barru and Meraja media, 2023)
[Full Paper] to pdf Copyright (c) 2023 Meraja journal